Reduced inflammation following human endometrial stromal/stem cell injection into male Wistar rats with cisplatin-induced acute kidney injury - Hadis Zeinali; Mahnaz Azarnia; Peyman Keyhanvar; Reza Moghadasali; Somayeh Ebrahimi-Barough; Majid Marandi-Kouchaki (BioImpacts, 2022)
Introduction: Inflammation is one of the most important mechanisms involved in cisplatin-induced acute kidney injury (AKI). Mesenchymal stromal/stem cells (MSCs) exhibit anti-inflammatory and immunomodulatory abilities. Human endometrial stromal/stem cells (hEnSCs) exhibit similar properties to MSCs. These cells secrete immunoregulators, so we investigated the inflammatory aspect of hEnSCs in the treatment of cisplatin-induced AKI in Wistar rats. Methods: Each group consisted of 6 male Wistar rats. Groups were as follows: sham, model (5 mg/kg cisplatin, IP), and treatment (1 million hEnSCs, IV, 3 hours after cisplatin). Renal function, histopathology, proliferation rate, infiltration of CD3+ T cell, and expression of Il-10 and cystatin c (Cst3) were assessed on day 5. DiI-labeled cells were tracked in kidney and liver on days 4 and 14. Results: HEnSC transplantation improved cisplatin-induced injuries such as renal dysfunction and tissue damage. The highest levels of pathologic scores and hyaline cast formation were observed in the model group while hEnSCs transplantation resulted in their reduction (154.00 ± 14.95, 8.00 ± 1.41 vs. 119.40 ± 5.43, 2.50 ± 1.05). The percentage of Ki-67 positive cells in the treatment group increased while cisplatin decreased proliferation (39.91 ± 5.33 vs. 23.91 ± 3.57 in glomeruli and 39.07 ± 2.95 vs. 16.61 ± 3.25 in tubules). The expression of Cst3 and Il-10 was higher in the model and treatment groups, respectively. DiI-labeled cells were observed in the renal tubules and liver lobes on days 4 and 14. Conclusion: HEnSCs may ameliorate cisplatin-induced AKI through anti-inflammatory and immunomodulatory effects and/or through paracrine effects.